Air quality meteorological and environmental information system in Western Macedonia, Hellas. (3rd March 2020) - Skordas, Ioannis A.; Triantafyllou, Athanasios G.; Fragulis, George F.
This paper aims to present the development of an operational, monitoring, as well as high-resolution local-scale meteorological and air quality forecasting information system for West Macedonia region, Hellas, in a dynamic, easily accessible and user-friendly way. The system, having been operated by the Laboratory of Atmospheric Pollution and Environmental Physics since 2002, has been in a continuous process of improvement. It consists of a structured system fully accessible and manipulable by users, as well as a system for accessing and managing measurement results in a direct and dynamic way. Thus, updates of the weather and air pollution forecast for the West Macedonia region are provided for the next seven days based on current day information. The forecasts are displayed through dynamic-interactive web charts, whereas there is also a visual illustration of the atmospheric pollution of the region in a map, using images and animation images. The application has been developed using state of the art web technologies (Ajax, Google Maps, etc.) and under an open-source software philosophy, allowing users to update the code according to their needs.